Natural Regeneration Capacity of Shorea leprosula Miq. at Gunung Dahu Research Forest in Bogor - Cut Ade Malinda; Prijanto Pamoengkas; Henti H Rachmat (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2022)
Shorea leprosula is one of the tree species within Dipterocarpaceae family which is a major source for timber production. The species has been planted massively in Gunung Dahu Research Forest (GDRF) in Leuwiliang- Bogor. Gunung Dahu Research Forest is a man-made dipterocarp forest which has varying slope class, topoghraphy and canopy cover. Furthermore, Natural regeneration is an important ecological factor in assessing the ability of forest regeneration, including in a plantation forest. Therefore, it is necessary to know the effect of slope and canopy cover on the regeneration of S. leprosula in order to characterize what factors support and constraint the naturally regenerating forest of Gunung Dahu Research Forest. Regeneration capacity of the species was observed in purposive plots which have been recorded for their flowering events. Seedlings were grouped into seedlings, and saplings. It was measured by census method in every slopes. Meanwhile, Variable observed included, number of available seedling at each slope category slope with its canopy cover, height and diameter of seedlings, and litter thickness. Regeneration capacity of the species was observed in purposive plots which had been recorded for their flowering events. Seedlings and saplings were taken using the census method. The results show that flat slope with shady canopy cover has the highest capacity of seedlings and the best growth. The uneven distribution of height and diameter indicates the need for silviculture action; such as, maintenance.